COMPETENCES OF EDUCATIONAL SYSTEM MANAGERS PEDAGOGICAL BASIS OF DEVELOPMENT (Journal of Science-Innovative Research in Uzbekistan, 2023)
Teaching using interactive methods, independent acquisition of all round scientific theoretical knowledge, formation of knowledge and skills and formation of scientific worldviews based on this, formation of teacher-student cooperation